2010
DOI: 10.2165/11539700-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Preventative Strategies for Early-Onset Bipolar Disorder

Abstract: Bipolar disorder is a chronic and typically recurring illness with significant psychosocial morbidity. Although the aetiological factors that contribute to the onset of mania, and by definition bipolar I disorder, are poorly understood, it most commonly occurs during the adolescent period. Putative risk factors for developing bipolar disorder include having a first-degree relative with a mood disorder, physical/sexual abuse and other psychosocial stressors, substance use disorders, psychostimulant and antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 165 publications
1
76
0
3
Order By: Relevance
“…This model was recently revised by McNamara et al [66]. The main difference is that only 3 stages were included; the unremitting/treatment-refractory course was not taken into account and the high-risk condition was placed at stage 1 rather than at stage 0, meaning that it is part of the illness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was recently revised by McNamara et al [66]. The main difference is that only 3 stages were included; the unremitting/treatment-refractory course was not taken into account and the high-risk condition was placed at stage 1 rather than at stage 0, meaning that it is part of the illness.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a number of suggestions as to stage-specific treatments [19,22,23,64,65,66,67]. A randomized controlled trial [73], confirmed by studies on psychoeducation [74], demonstrated the feasibility of early intervention aimed at recognizing prodromal symptomatology.…”
Section: Resultsmentioning
confidence: 99%
“…O3 may improve symptoms of many psychiatric disorders in youth including mood disorders (Wozniak et al 2007;Clayton et al 2009;McNamara et al 2010;Sarris et al 2012), autism (Amminger et al 2007), attention-deficit/hyperactivity disorder (ADHD) (Sinn and Bryan 2007;Sorgi et al 2007), and psychosis (Amminger et al 2010). O3 has also been shown to significantly improve cardiovascular and metabolic health and decrease body fat, both independently and in combination with regular exercise (Hill et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas combination treatment is also recommended for youth with BPSD (McClellan et al 2007;McNamara et al 2010), it has not been examined in children with BP-NOS/CYC in a controlled trial. Because of adverse effects with mood stabilizers, antipsychotics, antidepressants, and psychostimulants in pediatric BPSD, McNamara and colleagues have suggested that safer and well-tolerated interventions with demonstrated efficacy be used to treat prodromal/subsyndromal BPSD (McNamara et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Iako se izvestan broj istraživača zalaže za primenu farmakoterapije u stanjima povišenog rizika za psihozu, a usled boljeg daljeg toka bolesti i smanjenja broja relapsa, ovakav terapijski pristup može biti neadekvatan kada se radi o BAP [71,74]. Naime, agresivan terapijski pristup i lečenje početnih, asimptomatskih stadijuma BAP može dovesti do narušenja adaptivnih osobina i karakerisitka temperamenta koje mogu biti i deo bolesti pa je u terapiji BAP posebno važno razmišljati o funkcionalnosti pacijenta, a ne o kompletnoj stabilizaciji raspoloženja [12].…”
Section: Izazovi I Limitacijeunclassified